Identify high-risk DOR women ≤ 35 years old following assisted reproduction technology through cutoffs of anti-mullerian hormone and antral follicle counts - Yili Teng; Peipei Pan; Chang Liu; Yue Lin; Xiaozhu Zhu; Suichun Wu; Haiyan Yang; Xuefeng Huang; Fang Lian (BMC, 2024)
Abstract Background Females with diminished ovarian reserve (DOR) have significantly lower cumulative live birth rates (CLBRs) than females with normal ovarian reserve. A subset of young infertile patients, whose ovarian reserve is declining but has not yet met the POSEIDON criteria for DOR, has not received the attention it merited. These individuals have not been identified in a timely manner prior to the initiation of assisted reproductive technology (ART), leading to suboptimal clinical pregnancy outcomes. We categorized this overlooked cohort as the "high-risk DOR" group. Objective The primary aim of this study was to identify high-risk DOR patients through anti-Mullerian hormone (AMH) and antral follicle counts (AFCs). Methods A total of 10037 young women (≤ 35 years old) who underwent their first initial oocyte aspiration cycle at a single reproductive medicine center were included and further classified into three groups, based on the thresholds for AMH and AFC established through receiver operating characteristic (ROC) analysis and in alignment with the POSEIDON criteria. Two ROC analyses were performed to identify the cutoff values of AMH and AFC to obtain one viable embryo (one top-quality embryo or one viable blastocyst). The cutoffs of ROC were measured by sensitivity and specificity. The primary outcome was the cumulative live birth rate (CLBR) per oocyte aspiration cycle. The secondary outcomes included the number of oocytes retrieved and the number of viable embryos formed. Pearson's chi-square tests were conducted to compare the clinical outcomes among the three groups. Furthermore, univariate logistic regression analyses were performed to investigate the associations between ovarian reserve and clinical outcomes. All of the above comparisons between the high-risk DOR and NOR were further confirmed by propensity score matching (PSM) (1:1 nearest-neighbor matching, with a caliper width of 0.02). Results According to the ROC analyses and POSEIDON criteria, the present study identified a population of high-risk DOR patients (1.20 ng/mL < AMH values < 2.50 ng/mL, with 6 ≤ AFC ≤ 10; n = 682), and their outcomes were further compared to those of DOR patients (positive control, AMH values ≤ 1.2 ng/mL, and/or AFC ≤ 5; n = 1153) and of NOR patients (negative control, 2.5 ng/mL ≤ AMH values ≤ 5.5 ng/mL, and 11 ≤ AFC ≤ 20; n = 2649). Patients in the high-risk DOR group had significantly lower CLBRs than those in the NOR group (p < 0.001) but higher CLBRs than those in the DOR group (p < 0.001). Logistic regression further demonstrated that high-risk DOR was associated with a lower likelihood of cumulative live birth chance (OR 0.401, 95% CI: 0.332-0.486, p < 0.001) than NOR was, with a greater likelihood of cumulative live birth chance (OR 1.911, 95% CI:1.558-2.344, p < 0.001) than DOR was. To investigate the effects of embryo development stage, the outcomes of D3 embryos and blastocysts were analyzed separately. Significant differences in pregnancy outcomes were detected only in D3 embryo ET cycles among the three groups (high-risk DOR vs. NOR, all p < 0.05; DOR vs. NOR, all p < 0.05). DOR/high-risk DOR did not influence the pregnancy loss rates or pregnancy outcomes (clinical pregnancy rates and ongoing pregnancy rates) per positive HCG cycle (all p > 0.05). After PSM, the differences in ovarian response and pregnancy outcomes between the high-risk DOR and NOR groups were consistent with the results before PSM. Conclusion(s) Our study revealed that the CLBR of the high-risk DOR patients was significantly lower than that of females with normal ovarian reserve and greater than that of females with DOR. The values of AMH ranging from 1.2 to 2.5 and AFC ranging from 6 to 10 appeared to constitute meaningful thresholds in females with mildly reduced ovarian reserve.